Etiology of angiogenesis inhibition-related hypertension. (April 2015) - Lankhorst, Stephanie; Saleh, Langeza; Danser, AH Jan; van den Meiracker, Anton H
Highlights: Angiogenesis inhibition, targeting VEGF-signaling, is an established anticancer therapy. Development of sometimes severe hypertension is a common side effect. Decreased NO and increased ET-1 signaling are key-players in the development of hypertension. A shift of the pressure-natriuresis curve likely contributes to the maintenance of hypertension. Abstract : Angiogenesis inhibition, targeting vascular endothelial growth factor (VEGF) or its receptors, is an established treatment for solid tumors. A common side effect of this treatment is the development of sometimes severe hypertension. This hypertension is associated with a decrease in nitric oxide production, activation of the endothelin-signaling pathway and renin suppression. The mechanism underlying activation of the endothelin-signaling pathway is not fully understood. Both activation of endothelial cells and disinhibition of the VEGF-induced suppression of endothelin production by endothelial cells may be involved. The development of hypertension can be a reason to discontinue the angiogenesis inhibitor, thereby compromising anticancer treatment, but possibly is also a biomarker for a favorable antitumor response.